2019
DOI: 10.1371/journal.pone.0210761
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating animal-assisted therapy in mental health treatments for adolescents: A systematic review of canine assisted psychotherapy

Abstract: IntroductionAs interest in Animal-Assisted Interventions (AAI) grows, there is increasing need to differentiate informal activities from formal and professionally directed therapies, including mental health focussed Canine-Assisted Psychotherapy (CAP). There have been no reviews focusing exclusively on CAP and the distinct developmental period of adolescence. The aims of this study were to identify the characteristics of CAP interventions, their impacts and their acceptability, tolerability and feasibility for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 72 publications
(256 reference statements)
3
66
0
6
Order By: Relevance
“…These findings were consistent with existing research that found that HAEIs had a general positive impact on participants (Bowler et al, 2010). More specifically, HAEIs were shown to have a positive impact on special-education students' social abilities (Kim et al, 2012), autismspectrum symptoms, emotional well-being, and reduced behavioral issues and developmental delays in youth who were in need of special education support (Hoagwood, Acri, Morrissey, & Peth-Pierce, 2017;Jones, Rice, & Cotton, 2019;Nimer & Lundahl, 2007;O'Haire, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…These findings were consistent with existing research that found that HAEIs had a general positive impact on participants (Bowler et al, 2010). More specifically, HAEIs were shown to have a positive impact on special-education students' social abilities (Kim et al, 2012), autismspectrum symptoms, emotional well-being, and reduced behavioral issues and developmental delays in youth who were in need of special education support (Hoagwood, Acri, Morrissey, & Peth-Pierce, 2017;Jones, Rice, & Cotton, 2019;Nimer & Lundahl, 2007;O'Haire, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Animal-Assisted Interventions (AAI) have increased in prevalence in recent years ( Julius et al, 2013 ; O’Haire, 2017 ). Consequently, there has been increased research on the effectiveness and efficacy of different AAI approaches and predictors of outcomes across different populations ( O’Haire, 2017 ; Hu et al, 2018 ; Jones et al, 2019 ; Chitic et al, 2020 ). Dog-assisted interventions are among the most common AAI, likely due to a number of factors including, but not limited to, a dog’s accessibility, trainability, cost of care, and size ( Linder et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals, including dogs, have been known to respond in less predictable ways in the presence of these populations which can in some cases lead to increased risk ( Overall and Love, 2001 ; Yin, 2011 ). Nevertheless, dogs are commonly used in therapeutic settings and interventions with both children and individuals with disabilities ( Leonardi et al, 2017 ; Jones et al, 2019 ). Less is known about why some dog-child pairs clash (e.g., specific stimuli, strained interaction history, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also appears to influence people's environmental thinking and actions. The interaction between humans and animals encompasses a wide variety of physical, social, psychological, environmental, existential, and spiritual aspects, all of which have a positive impact on people's health and wellbeing and lead the individual to a functional whole [9,11,15]. This has led to increasingly extensive behavioral and neurophysiological studies on relations between humans and animals.…”
Section: Encounters With the Animalsmentioning
confidence: 99%